Principles & Practices of Management - (:unkn) unknown (ATLAS SkillTech University, 2025)
FYBSc Principles & Practices of Management Question Paper Semester 2
25BF204MPP
First Year Question Paper
Keywords: Principles & Practices of Management; Management